Measuring well-being: W3 indicators to complement GDP - Marco Giesselmann; Richard Hilmer; Nico A. Siegel; Gert G. Wagner (DIW Economic Bulletin, 2013)
Plenty of people in Germany, including politicians and researchers, believe that gross domestic product (GDP) is an outdated indicator of a society's prosperity. Therefore, at the end of 2010, the German Bundestag, the federal parliament, established a study commission (Enquete Kommission) tasked with developing an alternative to GDP for measuring growth, wealth, and quality of life. This commission has now submitted a proposal: to complement GDP with nine additional indicators, covering a wide range of areas such as the distribution of income, biodiversity, and life expectancy. Replacing gross domestic product with a single alternative index was rejected by the commission, however, since it is not possible to reduce citizens' very different wishes and expectations to a common denominator. The ten indicators cover three dimensions of wellbeing - economy, ecology, and social wealth - and hence are called W3 indicators.2 This name, which emphasizes the equal importance of the three dimensions, is concise and memorable enough to position itself alongside GDP. A representative survey of registered voters conducted by DIW Berlin and TNS Infratest shows that citizens generally consider all the new indicators proposed by the commission to be important. Respondents ranked preserving democracy and freedom as the most relevant indicator and further increasing life expectancy as the least relevant. Average per capita income - as an indicator of gross domestic product - is rated as the second least relevant factor. Moreover, the study also shows that opinions on the importance of different indicators vary considerably across socio-economic groups.
Keywords: B59; D63; H11; I32; Z18; 330; GDP; GDP and beyond; quality of life; Germany; TNS infratest; SOEP; W3 indicators